陳漢章《〈周禮〉行於春秋時證》析論: A Critical Study of Prevailing of the Book Zhouli during the Spring and Autumn Period of Chan Hanzhang - 許子濱 (人文中國學報, 2010)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 以《左傳》禮制印證《周禮》的古今論著中，最爲閎博的是陳漢章（1864—1938）的《〈周禮〉行於春秋時證》。此文前後三次刊載於不同刊物，兩次誤題黄侃所作。陳氏堅信《周禮》爲周公撰作，文中詳列《左傳》所載春秋遍行《周禮》的例證，共計七十三例，從而得出《周禮》於春秋之時廣泛頒行列國的結論。這些例證，主要爲彙集增補漢人（以鄭衆、鄭玄爲主）、唐人以至清人的注疏或論著而成。除少數例證值得懷疑外，绝大部分都能成立。經過通盤的驗證，《周禮》可與《左傳》互證共九十餘例，足以證明《周禮》部分禮文的制定確有事實依據。陳氏把這種現象解釋爲“《周禮》行於春秋時”的反映。但事實上，《周禮》與《左傳》有合有不合。陳説的可議之處在於，只見《周禮》與《左傳》的相通之處而忽視其間的差異，以致立論出現偏差。 Chan Hanzhang (陳漢章) (1864-1938) instead of Huang Kan (黄侃) (1886-1935) was the author of the captioned article. There has been much controversy on the book Zhouli (《周禮》) with its dating and authenticity in particular. Many scholars attempted to resolve the dating and authenticity of Zhouli based on the comparison of Zhouli and Zuozhuan (《左傅》), among them Chan Hanzhang’s article is the most noteworthy, yet little has been studied on his findings. This present article examines thoroughly Chan Hanzhang’s views on Zhouli from a perspective of intertextual cross-referencing. Indeed, Chan Hanzhang had made a careful comparison of the rituals contained in the Zuozhuan with those recorded in Zhouli. He concluded that Zhouli was written by Zhougong (周公) and was still prevailing during the Spring and Autumn period (770-453 BC). Although Zhouli and Zuozhuan agreed with each other in respect of various rituals, there are considerable discrepancies between these two classics.